LEVEL OF SOCIAL PHOBIA AMONG FACULTY OF PHYSICAL EDUCATION AND SPORTS SCIENCES STUDENTS AT KIRKUK UNIVERSITY - Ali Najmuldeen Abdulrahman; Hisham Salim Ibrahim; Aya Kamran Abdullah (Universitas Negeri Jakarta, 2025)
Background. The importance of the subject emerges from the fact that students of this college are exposed to repeated public performance situations such as practical presentations, skill tests, and arbitration, which are situations that increase the sensitivity to fear of negative evaluation and affect participation and academic performance. Objectives. This research aims to study the level of social phobia among students of the College of Physical Education and Sports Sciences at the University of Kirkuk, and to reveal the differences in its levels according to the gender variable. Method. Utilizing a descriptive-analytical methodology, data were gathered from prior experimental investigations and performance reports in sports, swimming, and cycling to assess biomechanical interventions. Results. The results showed that the students' level of social phobia was medium to high, with